Decision making under deep uncertainty for adapting urban drainage systems to change. Issue 6 (3rd July 2018) - Babovic, Filip; Mijic, Ana; Madani, Kaveh
ABSTRACT: Urbanisation and climate change are augmenting the uncertainty surrounding the future state of the world's water resource and are resulting in cities experiencing growing levels of risk of pluvial flooding. Drainage infrastructure is generally built using the paradigm of 'predict and optimise'; however, this approach fails to account for erroneous predictions. This can result in drainage systems delivering insufficient levels of flood protection. Irrespective of these uncertainties new drainage systems must be built, and existing ones adapted in such a way that they remain reliable. This work presents a critical analysis of the drivers of change of urban pluvial flooding and the uncertainties surrounding urban flood planning; thereby highlighting the shortcomings of current planning methodologies. Different Decision Making Under Deep Uncertainty (DMDU) frameworks are then explored and it is shown that they offer an improved ability to design reliable urban flood systems regardless of highly uncertain future conditions.